Designing Electronic Measuring Instruments by PC Microcomputer - Amaral Pereira, Wilton Ney; Martins Rezende, Ulysses; Carneiro Adami, Antonio Rodolpho; Azevedo, José Antonio (Revista Ciências Exatas, 2009)
This paper deals with a partnership example between two professional scholars with two productivefield specialists to conceiving and settlement an exclusive profile and innovative enterprise. In thispartnership is outstanding the high synergic potential of this kind of initiative, not many turned toaccount in Brazil, where, regardless occasional exceptions, the academic and the productive societysegments accomplish its tasks with reduced interaction. To actuate in the high-tech subjects, wherethe high scientific qualification human resources are essential, the productive field usually fall backon finished solutions, concerning themselves only with manufacturing process and choosing ratherthe foreign intellectual property. Otherwise, the academic world deals with knowledge researchnormally displaced with our industrial reality, local material resources or marketing demands. Thispaper explains the alliance of the four electronic engineers, half in college teaching and half inaction on the industrial and trading field, bringing financial resources and professional skills togetherto make an exclusively national enterprise.Key-words: enterprising, electronic, manufacturing, measurement, instrument.